2009
DOI: 10.1634/stemcells.2008-0866
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Fibroblastic Progenitor Cells in the Adult Mouse Lung Are Highly Enriched in the Sca-1 Positive Cell Fraction

Abstract: Originally identified as a marker specifying murine hematopoietic stem cells, the Sca-1 antigen has since been shown to be differentially expressed by candidate stem cells in tissues including vascular endothelium, skeletal muscle, mammary gland, and prostate of adult mice. In the adult murine lung, Sca-1 has previously been identified as a selectable marker for the isolation of candidate nonhematopoietic (CD45 Sca-1 1 CD34 1 cell phenotype does define endogenous clonogenic progenitor cells in the adult murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 31 publications
4
144
1
1
Order By: Relevance
“…The reduced infiltration of myeloid cells with an assumed profibrotic phenotype here after MSC therapy highlighted the importance of the proper function of the vascular system to avoid fibrosis development. Interestingly, a normal function of resident MSCs in adult lungs is crucial for pulmonary tissue homeostasis as they contribute to the maintenance of tissue integrity by various mechanisms (39,53,55). As an example, endogenous lung MSCs normally exert anti-inflammatory properties; these are, however, negatively affected by bleomycin treatment, thereby contributing to fibrosis development in a murine model of bleomycin-induced fibrosis (39).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 99%
“…The reduced infiltration of myeloid cells with an assumed profibrotic phenotype here after MSC therapy highlighted the importance of the proper function of the vascular system to avoid fibrosis development. Interestingly, a normal function of resident MSCs in adult lungs is crucial for pulmonary tissue homeostasis as they contribute to the maintenance of tissue integrity by various mechanisms (39,53,55). As an example, endogenous lung MSCs normally exert anti-inflammatory properties; these are, however, negatively affected by bleomycin treatment, thereby contributing to fibrosis development in a murine model of bleomycin-induced fibrosis (39).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 99%
“…Of interest, adult epithelial cells have been identified that have the ability to generate both bronchiolar and alveolar daughters in vitro (Kim et al, 2005;McQualter et al, 2010). The prospective isolation of adult lung stem cells is still in its early stages, and there is so far little consensus around the methods for cell isolation and culture, making it very hard to directly compare findings from different labs (see also, Summer et al, 2007;Teisanu et al, 2009Teisanu et al, , 2010McQualter et al, 2009;Rock et al, 2009). None of these prospectively isolated, putative adult stem cells has been reported to express any of the known embryonic multipotent epithelial cell markers.…”
Section: Embryonic and Adult Lung Progenitor Cells: Distinct Lineage-mentioning
confidence: 99%
“…Negative selection for the hematopoietic marker CD45 and the endothelial cell marker CD31, coupled with positive selection for Sca-1 and CD34, resulted in the generation of a cell fraction that was highly enriched in CCSP/Pro-SPC dual immunoreactive cells that retained epithelial character after serial passage in vitro. However, more recent studies suggest that Sca-1-positive populations can be further subdivided into high and lowexpressing subpopulations; Sca-1 low including Clara and bronchiolar stem cells (45), with Sca-1 high representing a lung stromal population (46). These fractionation strategies have been validated through use of mouse models, allowing expansion of bronchiolar stem cell pools and lineage tracing, yet suffer from the lack of in vitro assays allowing unambiguous classification of progenitor cell types based upon functional properties of isolated cells.…”
Section: Fractionation and In Vitro Culture Of Lung Epithelial Progenmentioning
confidence: 99%